The spy - Coelho, Paulo (Arrow Books, 2017)
When Mata Hari arrived in Paris she was penniless. Within months she was the most celebrated woman in the city. As a dancer, she shocked and delighted audiences; as a courtesan, she betwitched the era's richest and most powerful men. But as paronoia consumed a country at war, Mata Hari's lifestyle brought her under suspicion. In 1971, she was arrested in her hotel room on the Champs-EÌlyseÌes and accused of espionage. Told in Mata Hari's voice through her final letter, The Spy is the unforgettable story of a woman who dared to defy convention and paid the ultimate price.